Water scarcity effects on equitable water distribution and land use in a major irrigation project: case study in India - Gaur, Anju; Biggs, Trent W.; Gumma, Murali K.; Gangadhara Rao, Parthasaradhi; Turral, Hugh (2008)
In many river basins, upstream development and interannual variations in rainfall can cause both episodic and chronic shortages in water supplies downstream. Continued rapid development of surface and groundwater throughout the Krishna Basin in southern India resulted in historically low inflows to the main canals of the Nagarjuna Sagar irrigation project _8,955 km2_ during a recent drought _2002-2004_. This paper presents an integrated approach to assess how cropping patterns and the spatial equity of canal flow changed with water supply shocks in the left canal command area _3,592 km2_ of Nagarjuna Sagar. We combined 3 years _2000- 2003_ of canal release data with census statistics and high temporal resolution _8-10 days_ moderate resolution imaging spectrometer _MODIS_ 500-m resolution satellite imagery. The impact of water scarcity on land use pattern, delineated by MODIS images with moderate spatial resolution, was comparable with the census statistics, while the MODIS data also identified areas with changes and delays in the rice crop area, which is critical in assessing the impact of canal operations. A 60% reduction in water availability during the drought resulted in 40% land being fallowed in the left-bank canal command area. The results suggest that head reach areas receiving high supply rates during a normal year experienced the highest risks of fluctuations in water supply and cropped area during a water short year compared to downstream areas, which had chronically low water supply, and better adaptive responses by farmers. Contrary to expectations, the spatial distribution of canal flows among the three major zones of the command area was more equitable during low-flow years due to decreased flow at the head reach of the canal and relatively smaller decreases in tail-end areas. The findings suggested that equitable allocations could be achieved by improving the water distribution efficiency of the canal network during normal years and by crop diversification and introduction of alternative water sources during water shortage years. The study identified areas susceptible to decreases in water supplies by using modern techniques, which can help in decision-making processes for equitable water allocation and distribution and in developing strategies to mitigate the effects of water supply shocks on cropping patterns and rural livelihoods.